Similitude criterion derivation and pipe physical property test and suitable analysis for water hammner scale model of long distance district heating pipeline. (October 2017) - Hua, Jing; Zhang, Shigang; Fu, Lin
Highlights: Similarity criterions used in water hammer analysis is derived in the article. 7 different pipe are tested and compared in the article. A CHP system in Shanxi Province is taken as an example, and PB pipes are recommend in the scale experiment. Abstract: Based on a new district heating (DH) based on absorption heat exchangers, long distance district heating pipelines are developed rapidly in China. Water hammer protection is one of the most important design issues encountered in district heating pipeline safety. In order to analyze water hammer in DH pipe systems, scale models are introduced in this paper. Traditional similitude criterion numbers are derived from the motion equations based on the assumption of incompressible fluid. Therefore, traditional similitude criterion numbers are invalid in water hammer analysis, considering that water hammer is caused by the elasticity of the fluid. Therefore, similitude criterions used in water hammer analysis are derived by us and put forward in the article. In order to find out suitable pipes for scale models of DH pipeline systems, seven kinds of pipes are tested in an experiment based on typical parameters in DH pipeline systems. The results show that PB pipes should be used in shorter pipelines with small altitude difference, and air pressure pipes should be used in longer pipelines with large altitude difference. At last, a long distance transmission pipeline for a CHP system in Shanxi Province is taken as an example.